Improved Design Method of Emulsified Asphalt Cold Recycled Mixture - Chen, Zhang; Liang, Yuanlu; Yang, Jin; Xu, Tingyi; Sun, Lijun (Frontiers in Materials, 2020)
This paper proposes an improved design method of emulsified asphalt cold recycled mixture so as to solve the “secondary compaction” problem in cold recycled asphalt pavement. First, a temperature prediction equation is established based on measured data of cold recycled asphalt pavement. The equation provides the basis for improving the design method. Second, regarding the shortcomings of current design methods, here we introduce material design principles of emulsified asphalt cold recycled mixture and improve existing methods. Splitting strength (15 ℃) and unconfined compressive strength (60 ℃) are chosen as the basis of a double index to determine the asphalt emulsion content. Finally, the performance of the asphalt mixture designed by the improved design method is compared to that using the current specification of China. The results of the comparison validate that the proposed design method can effectively avoid early damage to cold recycled asphalt pavement.